DESAIN INFOGRAFIS: PENGEMBANGAN KREATIVITAS DAN LITERASI MEMBACA SISWA SD HATI KUDUS - Agustina, Noni (Jurnal Pengabdian Masyarakat AbdiMas, 2019)
Esa Unggul University conducted the community service at Hati Kudus Elementary School which is a private school in West Jakarta. It was selected because it required the development of creativity and reading literacy. Reading literacy is one of literacy programs determined by government and is expected to be a school life habit. Reading literacy activities is supposed to use the authentic reading sources in order to provide the factual information. The community service offered the authentic reading sources collaborated by onlineinfographic design application, thus, the students could absorb the information easily and presented their work using the interesting media. The community service could answer the school problem in enhancing the students’ creativity and reading literacy. The methods used were lecturing, exploring the application, simulating, discussion, demonstrating, and presenting the students’ work. The result showed that the students devoted their reading into infographic design work. They were enthusiastic by choosing the interesting features and they felt easily to present their work. It is expected to be an alternative solution in developing student’s creativity and reading literacy to be more authentic, meaningful, and interesting. Keywords: Infographic design, creativity, reading literacy.